Unexpected solvent effects on the UV/Vis absorption spectra of o-cresol in toluene and benzene: in contrast with non-aromatic solvents. Issue 3 (14th March 2018) - Zheng, Dong; Yuan, Xiang-Ai; Ma, Haibo; Li, Xiaoxiong; Wang, Xizhang; Liu, Ziteng; Ma, Jing
Abstract : Cresol is a prototype molecule in understanding intermolecular interactions in material and biological systems, because it offers different binding sites with various solvents and protonation states under different pH values. It is found that the UV/Vis absorption spectra of o -cresol in aromatic solvents (benzene, toluene) are characterized by a sharp peak, unlike the broad double-peaks in 11 non-aromatic solvents. Both molecular dynamics simulations and electronic structure calculations revealed the formation of intermolecular π-complexation between o -cresol and aromatic solvents. The thermal movements of solvent and solute molecules render the conformations of o -cresol changing between trans and cis isomers. The π-interaction makes the cis configuration a dominant isomer, hence leading to the single keen-edged UV/Vis absorption peak at approximately 283 nm. The free conformation changes between trans and cis in aqueous solution rationalize the broader absorption peaks in the range of 260–280 nm. The pH dependence of the UV/Vis absorption spectra in aqueous solutions is also rationalized by different protonation states of o -cresol. The explicit solvent model with long-ranged interactions is vital to describe the effects of π-complexation and electrostatic interaction on the UV/Vis absorption spectra of o -cresol in toluene and alkaline aqueous (pH > 10.3) solutions, respectively.